2009
DOI: 10.1152/ajpcell.00668.2008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Kv1.3 potassium current by phosphoinositides and stromal-derived factor-1α in Jurkat T cells

Abstract: The activation of Kv1.3 potassium channel has obligatory roles in immune responses of T lymphocytes. Stromal cell-derived factor-1alpha (SDF-1alpha) binds to C-X-C chemokine receptor type 4, activates phosphoinositide 3-kinase, and plays essential roles in cell migration of T lymphocytes. In this study, the effects of phosphoinositides and SDF-1alpha on Kv1.3 current activity were examined in the Jurkat T cell line using whole cell patch-clamp techniques. The internal application of 10 microM phosphatidylinosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The association between the Src‐family tyrosine kinase Lck and Kv1.3 is necessary for the initiation of the TCR‐mediated signaling triggered during the formation of the immune synapse 6–8 and has been reported in other, non‐TCR‐dependent, T‐cell responses as well 9–11. Therefore, we explored whether a differential Lck activation in iTregs may concur with the loss of control of Kv1.3 activity by TCR.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The association between the Src‐family tyrosine kinase Lck and Kv1.3 is necessary for the initiation of the TCR‐mediated signaling triggered during the formation of the immune synapse 6–8 and has been reported in other, non‐TCR‐dependent, T‐cell responses as well 9–11. Therefore, we explored whether a differential Lck activation in iTregs may concur with the loss of control of Kv1.3 activity by TCR.…”
Section: Resultsmentioning
confidence: 89%
“…We next wanted to address the question of whether the relocalization and clustering of Lck to the IL‐2‐R complex in iTregs encompassed the regulatory switch of Kv1.3 activity. The functional incidence of Kv1.3 spatial redistribution has been already documented in T cells 6–11. In order to examine whether the TCR‐dissociated Kv1.3 becomes functionally linked to the highly active IL‐2‐R complex, we performed high‐throughput patch clamp analysis with sorted iTregs incubated with IL‐2, IL‐6 or IL‐10.…”
Section: Resultsmentioning
confidence: 99%
“…Including PIP3 in the pipette solution in cells exposed to dofetilide for 5 hours reversed AP prolongation (Figure 2D) and inhibited afterdepolarizations; as reported by others, this effect was very rapid. 7,16 Action potentials recorded from control cells with PIP3 in the pipette were no different from action potentials recorded without PIP3 in the pipette. Figure 2E summarizes the frequency of afterdepolarizations in cells studied ≥5 hr after isolation (controls, 0/15), cells exposed to dofetilide for 5 hr after isolation (15/19), and cells exposed to dofetilide for 5 hr after isolation and studied with PIP3 in the pipette (2/15).…”
Section: Resultsmentioning
confidence: 90%
“…The Kv1.3 channel is important in the activation and function of effector memory T cells (Gilhar et al, 2011 ). Recently, it was reported that PIP 2 applied through patch pipettes in whole-cell recordings significantly reduced Kv1.3 currents in Jurkat T cells and this regulation may be significant for the maintenance of T lymphocyte activation in immune responses (Matsushita et al, 2009 ). However, the mechanisms of this modulation need to be further explored.…”
Section: Voltage-gated Potassium Channelsmentioning
confidence: 99%